SOME WAYS TO INCREASE CIVIL SOCIETY PARTICIPATION IN ENSURING POLITICAL SECURITY IN MONGOLIA - Nergui Bayartogtokh; Bazarsuren Jantsanzemuu; Enkhjargal Bayasgalan; Munkh-Erdene Navaan (International Journal of Innovative Technologies in Social Science, 2024)
Political security is about the organizational stability of states i.e. The systems of government and the ideologies that give governments, and states, their legitimacy. Political sector threats target the organizational stability and sovereignty of the state. Although they may originate from (or be aimed at) the military, societal, economic, environmental and/or the political sectors, to be classified as political threats, they must threaten the organizational stability of the state without using massive military, identification, economic, or environmental means. Their objectives range from pressuring governments to behave in a certain manner on policy matters to overthrowing governments or provoking separatism and preparation for war.1 The values and nature of the civil society are aimed at protecting the interests of the country and citizens, improving the quality of life, and ensuring sustainable development. The main issue of political security is the protection of the political interests of the country and its citizens, a set of measures, the governmental and non-governmental organizations it is aimed at the sustainable development of the country and the improvement of the quality of people’s life as well as the form of governance, state management mechanisms and political forces, state, leaders of state and all of these are aimed at creating a political system. When we are considering the participation of civil society in security activities, firstly political security is considered in the framework of this research.